Government expenditure and economic growth in Malaysia - Doris binti, Arichat Enggoh (Universiti Malaysia Sarawak (UNIMAS), 2006)
The study set out to investigate the causality pattern between economic growth and government expenditure during period 1960 to 2004 in Malaysia. Furthermore, it indicates the research of long run equilibrium by using the Johansen’s cointegration procedures. In this research, the Granger causality technique is being adopted for two specifications of models: linear model and double logarithm model. In comparison to both results, it tends to support the Wagner’s law, which the government expenditure causes the economic growth in Malaysia. These empirical tests have shown that the economic growth is strongly endogenous for Malaysia.